2016
DOI: 10.17582/journal.sja/2016.32.3.218.222
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Yield Response of Five Elite Grass Pea (Lathyrus sativus L.) Genotypes to Varying Levels of Potassium

Abstract: P ulses are considered as one of the most important sources of vegetable protein for the human life and animals and consumed by people of all ages and all levels. In Pakistan, pulses occupy about 5% area under cultivations. Owing to rapid increase in population and the importance of pulses in human diet and health, the interest for growing pulses is increasing day by day (FAO, 2016). Pea is a highly nutritious crop which is globally grown as a winter crop (Ali et al., 2002), such as in tropics and subtropics i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…Akhter et al [14] reported that plant height increased with increasing rates of potassium. These results are in accordance with Leghari et al [15], who found that increasing of potassium markedly increased the growth of peas. The interaction effect of different levels of potassium and varieties were statistically significant affect the plant height.…”
Section: Plant Heightsupporting
confidence: 93%
See 1 more Smart Citation
“…Akhter et al [14] reported that plant height increased with increasing rates of potassium. These results are in accordance with Leghari et al [15], who found that increasing of potassium markedly increased the growth of peas. The interaction effect of different levels of potassium and varieties were statistically significant affect the plant height.…”
Section: Plant Heightsupporting
confidence: 93%
“…However, the combined effect of variety and potassium on the number of primary branches plant -1 was statistically non-significant (Table 3). Leghari et al [15], showed their study that interaction effect of variety and potassium was insignificant.…”
Section: Branches /Plantmentioning
confidence: 98%
“…The yield of mungbean cultivars was maximized when 90 kg potassium was added per hectare (Hussain et al, 2011). Laghari et al (2016) observed an increasing seed yield with each increasing level of potassium. It has been reported in previous studies that potassium is the factor for increased development and yield of mungbean crop (Chanda et al, 2002;Fadhel et al, 2011).…”
Section: Introductionmentioning
confidence: 84%
“…This may be due to the synergistic effect of the supplied nutrients, an increase in the photosynthetic activity of plants, the formation of more organic compounds and their more efficient use by plants in the process of seed formation and filling [40]. At the same time, additional plant nutrition with nitrogen during the growing season can enhance the growth of the vegetative part of the plant, extend the period of active functioning of the leaf surface and increase the level of nutrient supply to the seeds during the filling and maturation phase [41]. In general, our experiment showed the highest efficiency of the tested factors with the complex application of mineral fertilizers at a rate of N 30 P 45 K 45 + N 15 and the microbial preparation Rhizogumin.…”
Section: Discussionmentioning
confidence: 99%